PEMBERDAYAAN MASYARAKAT DESA WISATA PANDEAN UNTUK PEMBANGUNAN BERKELANJUTAN DI WILAYAH KECAMATAN DONGKO - Chilmi, M. Zuhriyan; Armanda, Henda (Jurnal Master Pariwisata (JUMPA), 2023)
Aspect of accessibility and geographical contours. From the aspect of accessibility, Pandean Village is easy to access because it is passed by the route between Trenggalek-Pacitan Regencies. Meanwhile, from a geographical aspect, the Pandean Village area which has mountainous contours adds to the beauty and special features of Pandean Village. This research aims to exploit the development potential of Pandean Village as a tourist village based on a study of aspects of readiness and demand so as to be able to provide recommendations for the sustainable development of Pandean Village. The approach used in this study is a mixed method including qualitative methods to examine supply aspects, community characteristics, policies, and quantitative methods to examine tourism demand aspects. The results of the study show that Pandean Village has the potential to be developed as a sustainable tourism village. However, there are various problems in Pandean village such as convenience, information, support from the village government and institutions that are still new and a lack of knowledge in tourism development. Keywords: tourist village; community economy; sustainable